Incidencia de la pesca artesanal en la contaminación de la Playa del Cantón Puerto López, de la Provincia de Manabí - Ecuador - Osejos Merino, Miguel Ángel (2017)
The following research was conducted on the beach of Puerto Lopez town located in the province of Manabí. In this research the impact of artisanal fisheries in the pollution of the beach during the months of February to July of this year. The information was collected using signing, direct observation and survey. As results of this study ten areas of fishing, where fishermen perform their work, having greater incidence of fishing cauldrons of Bollita and Punta Mala, fishing gear used by artisanal fishermen are varied, being the most used, trammel surface and bottom, these gear used in artisanal fishing activity suggest evidence of contamination residue of different type in beach areas the same that cause air pollution and this can be perceived in different areas of the beach odors also harm marine species, the combination of these problems end not pretty the place, what is a tourist place visited. With the analysis of these results we proceeded to raise the proposed Fishery Management Plan for artisanal fishermen of Puerto Lopez town.